Andreou, Kostas - (:unkn) unknown (My University, 2026)
Dr. Kostas Andreou is an Agronomist who graduated from the School of Agriculture at the Aristotle University of Thessaloniki with a specialization in Plant Protection. He holds an MSc in Environmental Sciences from the University of Lancaster, Lancaster Environment Centre, UK and a PhD from the same university with specialization in the fate and behavior of organic pollutants in soils. On his return to Cyprus he worked as a consultant in an environmental consulting firm. During the academic year 2008-2009 he worked as a postgraduate assistant in the Soil science laboratory at the Department of Environmental Science and Technology, Cyprus University of Technology. Since 2009 he works as a Special Teaching Staff in the Department of Environmental Science and Technology, Cyprus University of Technology. His research interests include among others the areas of fate and behavior of pollutants in soil, soil ecotoxicology, soil remediation, management of organic matter in soils, environmental impact assessment, management of environmental information and ecological risk management.
Keywords: Soil; Environmental impact assessment; Environmental riskassessment; Ecotoxicology; Soil remediation; Chemicals management